2009
DOI: 10.3945/jn.109.104968
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Pattern Characterized by High Intake of Vegetables, Fruits, and Vegetable Oils Is Associated with Reduced Risk of Preeclampsia in Nulliparous Pregnant Norwegian Women

Abstract: Several dietary substances have been hypothesized to influence the risk of preeclampsia. Our aim in this study was to estimate the association between dietary patterns during pregnancy and the risk of preeclampsia in 23,423 nulliparous pregnant women taking part in the Norwegian Mother and Child Cohort Study (MoBa). Women participating in MoBa answered questionnaires at gestational wk 15 (a general health questionnaire) and 17-22 (a FFQ). The pregnancy outcomes were obtained from the Medical Birth Registry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
232
4
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(266 citation statements)
references
References 44 publications
20
232
4
10
Order By: Relevance
“…Even in the presence of exposure to PAHs, the MDA levels might not increase in pregnant women who consume at least seven servings per day of fruit and vegetables. Considering that previous studies have shown reduced risk of preeclampsia with higher intake of fruit and vegetables (Longo-Mbenza et al, 2008;Brantsaeter et al, 2009), the findings of our study can be utilized in health and nutrition promotion or nutrition education programs to help prevent adverse pregnancy outcomes. Further studies are warranted to explore the mechanisms underlying the negating action of the fruit, vegetable and vitamin C intakes on the relationship between PAH exposure and oxidative stress, and the implications of these results in relation to adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the presence of exposure to PAHs, the MDA levels might not increase in pregnant women who consume at least seven servings per day of fruit and vegetables. Considering that previous studies have shown reduced risk of preeclampsia with higher intake of fruit and vegetables (Longo-Mbenza et al, 2008;Brantsaeter et al, 2009), the findings of our study can be utilized in health and nutrition promotion or nutrition education programs to help prevent adverse pregnancy outcomes. Further studies are warranted to explore the mechanisms underlying the negating action of the fruit, vegetable and vitamin C intakes on the relationship between PAH exposure and oxidative stress, and the implications of these results in relation to adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up is conducted by questionnaires at regular intervals and linkage to national health registries (25,26) .…”
Section: The Norwegian Mother and Child Cohort Studymentioning
confidence: 99%
“…Healthy dietary patterns during pregnancy have been associated with reduced risk of adverse pregnancy and birth outcomes (4,5) . It is therefore concerning that suboptimal dietary quality has been consistently reported during pregnancy, reflecting poor adherence with dietary guidelines (6,7) .…”
mentioning
confidence: 99%